(untitled) (diségno, 2018)
It was important for the first Focus of the 2017 UID Convention in Naples to be centered on the theme of the identity of drawing in terms of temporal evolution. It is the first reflection that we participants are called to face and that we “must” know how to deal with. The first question we ask ourselves, coherently with what is requested of us, is, in fact, how we stand today in the context of an evolution that has important repercussions even on teaching –if there has actually been an evolution– and how we relate to its undeniable metamorphoses or, more properly, “mutations” as Darwin would call them.